Regulation of the Signal-Dependent E Protein HEBAlt Through a YYY Motif Is Required for Progression Through T Cell Development - Yoganathan, Kogulan; Yan, Anqi; Rocha, Juliana; Trotman-Grant, Ashton; Mohtashami, Mahmood; Wells, Lisa; Zúñiga-Pflücker, Juan Carlos; Anderson, Michele K. (Frontiers in Immunology, 2022)
The E protein transcription factors E2A and HEB are critical for many developmental processes, including T cell development. We have shown that the Tcf12 locus gives rise to two distinct HEB proteins, with alternative (HEBAlt) and canonical (HEBCan) N-terminal domains, which are co-expressed during early T cell development. While the functional domains of HEBCan have been well studied, the nature of the HEBAlt-specific (Alt) domain has been obscure. Here we provide compelling evidence that the Alt domain provides a site for the molecular integration of cytokine signaling and E protein activity. Our results indicate that phosphorylation of a unique YYY motif in the Alt domain increases HEBAlt activity by 10-fold, and that this increase is dependent on Janus kinase activity. To enable in vivo studies of HEBAlt in the T cell context, we generated ALT-Tg mice, which can be induced to express a HA-tagged HEBAlt coding cassette in the presence of Cre recombinases. Analysis of ALT-Tg mice on the Vav-iCre background revealed a minor change in the ratio of ISP cells to CD8+ SP cells, and a mild shift in the ratio of T cells to B cells in the spleen, but otherwise the thymus, spleen, and bone marrow lymphocyte subsets were comparable at steady state. However, kinetic analysis of T cell development in OP9-DL4 co-cultures revealed a delay in early T cell development and a partial block at the DN to DP transition when HEBAlt levels or activity were increased. We also observed that HEBCan and HEBAlt displayed significant differences in protein stability that were resolved in the thymocyte context. Finally, a proteomic screen identified STAT1 and Xpo1 as potential members of HEBAlt-containing complexes in thymocytes, consistent with JAK-induced activation of HEBAlt accompanied by translocation to the nucleus. Thus, our results show that the Alt domain confers access to multiple layers of post-translational control to HEBAlt that are not available to HEBCan, and thus may serve as a rheostat to tune E protein activity levels as cells move through different thymic signaling environments during T cell development.